Research on multi-objective emergency logistics vehicle routing problem under constraint conditions - Miaomiao Du; Hua Yi (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: Aim at choosing a relative good vehicle routing in emergency conditions under constraint conditions when disaster happens. Rapid response and rescue can save a lot of people. Design/methodology/approach: Modeling analysis: establishing a mathematical model of multi-objective emergency logistics vehicle routing problem. And in end of the paper, we intend to use genetic algorithms to solve the problem. Findings: Considering time requirement and cost limit both while choosing vehicle routing when the disasters happens is meaningful. We can get a relative good result and give a guidance to rescue teams. Originality/value: Consider cost and time objectives and kinds of realistic conditions (such as the road congestion) in the model when solving the problem, having expanded the theory scope.
Keywords: 650; Emergency Logistics; Road Congestion; Unilateralism Time Window; Vehicle Routing Problem; Genetic Algorithms